2004
DOI: 10.1029/2003jd004402
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range transport of Asian pollution to the northeast Pacific: Seasonal variations and transport pathways of carbon monoxide

Abstract: [1] Continuous CO measurements were obtained at Cheeka Peak Observatory (CPO, 48.3°N, 124.6°W, 480 m), a coastal site in Washington state, between 9 March 2001 and 31 May 2002. We analyze these observations as well as CO observations at ground sites throughout the North Pacific using the GEOS-CHEM global tropospheric chemistry model to examine the seasonal variations of Asian long-range transport. The model reproduces the observed CO levels, their seasonal cycle and day-to-day variability, with a 5-20 ppbv ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
358
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(384 citation statements)
references
References 85 publications
(171 reference statements)
25
358
1
Order By: Relevance
“…Boreal forest fires, most frequent in Canada and Siberia (Spichtinger et al, 2004), occur mainly from May to October (Lavoué et al, 2000). The location of Siberian emissions is in agreement with Liang et al (2004) who indicate that summertime 380 emissions from boreal forest fires are exported at latitudes higher than 55°N, what is confirmed by Spichtinger et al (2004) with the highest concentrations above Siberia found at latitudes up to 70°N. Extreme CO concentrations (as high as 800 ppbv) were measured around Lake Baikal at 8.0-12.5 km altitude (Nedelec et al, 2005).…”
supporting
confidence: 65%
“…Boreal forest fires, most frequent in Canada and Siberia (Spichtinger et al, 2004), occur mainly from May to October (Lavoué et al, 2000). The location of Siberian emissions is in agreement with Liang et al (2004) who indicate that summertime 380 emissions from boreal forest fires are exported at latitudes higher than 55°N, what is confirmed by Spichtinger et al (2004) with the highest concentrations above Siberia found at latitudes up to 70°N. Extreme CO concentrations (as high as 800 ppbv) were measured around Lake Baikal at 8.0-12.5 km altitude (Nedelec et al, 2005).…”
supporting
confidence: 65%
“…Typically during spring, trans-Pacific transport of pollutants to the western U.S. is at its maximum, which brings high concentrations of CO 2 from emission sources in Asia (Jaffe et al, 1999;Stohl et al, 2002;Liang et al, 2004;Jaffe et al, 2005;Zhang et al, 2008;Fischer et al, 2009;Lin et al, 2012;Gratz et al, 2015). It is interesting to note that in the AprMay case, cluster 1 includes a case of FT Asian long-range transport with subsidence of the air mass to MBO.…”
Section: Case Study: Asian Long-range Transport Event At Mbo -4/19/2014mentioning
confidence: 99%
“…S2 and S3 also show height and average trajectory maps for each cluster, respectively. By choosing April and May for these clustered trajectories, we increased the likelihood of influence by mid-latitude cyclones and the Pacific High Pressure system that circulates air off the Pacific coast (Stohl et al, 2002;Liang et al, 2004;Zhang et al, 2008). Cluster 1 shows relatively high CO 2 , O 3 , and pressure and low average water vapor.…”
Section: -Year Overall Analysismentioning
confidence: 99%
“…These observations have mainly focused on the upper troposphere, thus providing very limited aircraft measurements in the middle troposphere over the western North Pacific. Model simulations showed that export of anthropogenic gases from the Asian continent to the western Pacific through the middle troposphere above the planetary boundary layer is particularly important for the transpacific transport (e.g., Liang et al, 2004;Sawa et al, 2007). Thus, more systematic and longterm measurements in the middle troposphere by using regular aircraft observations are still needed to better understand the widespread dispersion of trace gases emitted from Asian sources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, growth of carbon dioxide (CO 2 ) emissions from fossil-fuel burning and industrial processes has been accelerating in East Asia, particularly in China (Gregg et al, 2008). Carbon monoxide (CO) and other gaseous pollutants emitted from East Asia affect not only the regional environment over the western North Pacific (e.g., Sawa et al, 2007;Wada et al, 2011) but also the air quality over the North American continent as a result of the transpacific transport (e.g., Liang et al, 2004). Agricultural activities in Asian regions are also important as major sources in the global budgets of methane (CH 4 ) (Bergamaschi et al, 2009) and nitrous oxide (N 2 O) (Huang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%